Pengaruh Kualitas Pelayanan dan Lokasi terhadap Kepuasan Pelanggan Distributor Beauty Glow Skincare Trenggalek - Silvi Ayu Firnanda; Imam Sukwatus Suja’i (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to determine the effect of service quality on customer satisfaction, determine the effect of location on customer satisfaction, and to determine the effect of Service Quality and Location on Customer Satisfaction of Beauty Glow Skincare Trenggalek Distributor. The number of samples in this study amounted to 110 respondents. The results of this study indicate that partially Service Quality has a positive and significant effect on Customer Satisfaction with a tcount> ttable value of 10.311> 1.982, partially Location has a positive and significant effect on Customer Satisfaction with a tcount<ttable value of 5.157> 1.982, simultaneously quality service and location have a positive and significant effect on customer satisfaction with a value of Fcount>Ftable, namely 80.989>3.09. The coefficient of determination value of 59.5% shows that Service Quality and Location affect Customer Satisfaction and the remaining 40.5%.